Tanda Keberadaan Tidak Langsung Kelelawar Pemakan Buah Di Sub Blok Perhutanan Sosial Hutan Pendidikan Konservasi Terpadu Tahura Wan Abdul Rachman - Edo Firnanda; Agus Setiawan; Elly Lestari Rustiati; Eka Sulpin Ariyanti (Jurnal Sylva Lestari, 2015)
Study on fruit bats' food remains was conducted in Sub Blok Perhutanan Sosial Hutan Pendidikan Konservasi Terpadu Tahura Wan Abdul Rachman in December 2014 - March 2015. Direct survey was done for indirect signs and mist net for bat species. Three bats species found were family Pteropodidae, Cynopterus horsfieldii, Cynopterus sphinx and Macroglossus sobrinus. Seven food remains identified were six fruits and one leaf. The food plants are luwingan (Ficus hispida), duku (Lancium domesticum), jambu bol (Syzygium malaccense), jambu air (Syzygium aqueum), jambu biji (Psidium guajava), ketapang (Terminalia cattapa), and dadap (Erythrina lithosperma). Luwingan (Ficus hispida) is the most consumed. Keywords: Fruit bats, indirect signs, hutan pendidikan konservasi terpadu, Tahura Wan Abdul Rachman